Terahertz Frequency Domain Response for Insulation State Assessment of Vehicle Cable Terminal Under Electro-Thermal Aging - Binglei Cao; Shuaibing Li; Yi Cui; Dong Yang; Yongqiang Kang; Baopeng Lu; Guangning Wu (CSEE Journal of Power and Energy Systems, 2025)
To accurately diagnose the aging condition of the vehicle-mounted high-voltage cable terminals under the combined electro-thermal stress, this paper proposes a terahertz frequency spectrum technology-based method. First, an electro-thermal aging platform is established in the laboratory to obtain the test samples of ethylene-propylene rubber (EPR) cable terminals with different aging gradients. Then, the degree of electro-thermal aging is characterized by frequency spectrum, absorption coefficient spectrum, absorption spectrum, refractive index and dielectric constant in the terahertz domain. Moreover, the micro-morphology and micro-area structure of the test samples under different aging gradients are also observed by scanning electron microscopy, and both the material and chemical properties are analyzed. The findings demonstrate that terahertz frequency spectra offer significant benefits in non-destructively detecting and identifying the insulation condition of vehicle cable terminals during electro-thermal aging. Laboratory tests confirm the feasibility of utilizing the terahertz frequency spectrum to assess the insulation aging state of EPR cable terminals, making it potentially applicable for on-site purposes.